Řeholní kongregace v Čechách na přelomu 19. a 20. století v kontextu proměn náboženského milieu - Miroslav Novotný (Theatrum Historiae)
Opening part of this article presents the transformation and character of religious milieu in Central and Western Europe in 19th and at the beginning of 20th century (especially the processes of de-ethatization of religion, secularization and de-christianization, respectively the so-called second confesionalization). With regard to the focus of this work, the main attention is paid to the processes running inside the Catholic Church. It deals more precisely also with the similar development in the western part of the Austro-Hungarian monarchy. It views complex situation in Czech lands in a wider context of transformations and creation of the modern European industrial society in the second half of the 19th century, which also strongly mirrored in the activity of individual Churches and led, among others, to the “religious renaissance” and to the search for new or renewed forms of religious activities, as well as spiritual life and also to the formation of new regular communities (men and especially women congregations) together with lay confraternities (Marian communities, in the first place). Second part of the work demonstrates the processes on the model example of the mostly agrarian and traditionally conservative South Bohemia. Beginning of the new times is in the Budweiser diocese, the traditional catholic bulwark in Bohemia, connected first of all with the episcopacy of Jan Valerian Jirsik. It is also thanks to his commitment and work that the status of Catholicism in the whole region significantly improved and that in the second half of the 19th and first half of 20th century, the South Bohemian diocese became the place of foundation or activity of quite a number of regular and lay religious communities.